Mobilidade diafragmática e biomecânica da deglutição em pacientes com doença pulmonar obstrutiva crônica - Brancher, Elizabeth do Canto (2017)
A hyperinflation caused by chronic obstructive pulmonary disease (COPD) promotes diaphragmatic rectification, reducing a zone of apposition of the diaphragm and length of muscle fiber, resulting in loss of muscle contraction, respiratory muscle strength. Chronic lung diseases tend to be non-specific, as does compensation to maintain a respiratory function. However, this mechanism reduces airway protection, facilitating pulmonary penetration or aspiration. The present study aimed to relate the biomechanics of swallowing and the diaphragmatic mobility of subjects with COPD. It is an observational, transversal and descriptive study involving 19 COPD subjects. Body mass index, airflow obstruction, dyspnea and exercise capacity (BODE), diaphragmatic mobility and videofluroscopy of swallowing, body mass index, airflow obstruction, disability and capacity of exercise. The results showed that dysphagic subjects (n = 3) had mild (n = 2) and moderate / severe (n = 1) dysphagia. Subjects who presented null swallowing in a discrete manner did not present diaphragmatic mobility, while the subject with moderate / severe dysphagia presented low diaphragmatic mobility. There was a moderate negative relation between the pharyngeal transit time and diaphragmatic mobility in the net consistency (r: -0.508, p: 0.02). This work contributed with unpublished findings regarding diaphragmatic mobility and risk of deferment. And so, nasíl new researches on the subject with the objective of clarifying this relation better and improvements for the subjects with COPD.